Advances in targeted retinal photocoagulation in the treatment of diabetic retinopathy - Lin, Zichun; Deng, Aijun; Hou, Ning; Gao, Liyu; Zhi, Xushuang (Frontiers in Endocrinology, 2023)
Aim: Targeted retinal photocoagulation (TRP) is an emerging laser technology for retinal targeted therapy. TRP can specifically act on unperfused retinal capillaries and retinal intermediate ischemic areas, reduce damage to tissue perfusion areas and panretinal photocoagulation (PRP) complications or adverse events. In this regard, this review discusses the treatment options, efficacy, and latest progress of TRP for diabetic retinopathy (DR) based on randomized controlled trial (RCT), meta-analysis, case review, and other existing studies. Methods: In-depth research was conducted on articles about the proposal and development of TRP, its simple application in DR, and combined therapy. In order to review the new progress, application methods, effects, and prospects of TRP in the treatment of DR, the articles related to TRP in the databases of PubMed and Web Of Science since this century were comprehensively analyzed. Results: TRP is effective in treating DR and may become a substitute for PRP in the future. In addition, the treatment regimen of TRP combined with intravitreal injection of anti-vascular endothelial growth factor (anti-VEGF) drugs can also be used as a new therapeutic approach to expand the treatment regimen for the treatment of DR, and this combination therapy also has effects on other retinal vascular diseases. Conclusions: With the advancement of technology, TRP has been continuously applied in clinical practice, and its potential benefits have opened up broad prospects for the treatment of DR. The combination therapy of TRP and anti-VEGF is expected to become a new option for patients with DR and retinal diseases.